Health economics research: prospects and challenges in Nigeria (2013)
This paper traces the evolution and development of health economics as a research and academic discipline in Nigeria. The emergence of research in health economics as a discipline in Nigeria in the 1980s through the international funding agencies’ activities predates its teaching. The funding was basically channelled to support capacity building in health policy research and training in the country. The subsequent critical mass of trained health economists produced went on to initiate the teaching of the discipline in Nigerian universities, from which Masters and Ph.D graduates have been produced. The course is mainly taught at the postgraduate level in the few Nigerian universities offering the discipline. Furthermore, the estimation of the two rounds of NHAs for the country has been facilitated by the domestic capacity in health economics, with domestic and foreign financial support. The paper identified two classes of health economics research in Nigeria: the research type, based on university or research institute, and the demand- driven research or consultancies. These are anchored by two main axes of university and/or research institute-based health economics research in Nigeria: Ibadan axis and Enugu axis. As a follow-up to the global and regional associations of health economists, the paper points to the emergence at national level of the Nigerian Health Economics Association which provides a platform for collaboration among health economists in the country. Despite the progress thus far, a number of challenges confront the research landscape of health economics in Nigeria, which include poor data availability, and reluctance to release data, as well as limited number of trained health economists. There is therefore the need for the political will to fully implement the health management information system project, enforce the Freedom of Information Act; and the provision of funds needed to support postdoctoral research in health economics.